Priority Policies And Program Of UIN Sunan Gunung Djati Bandung Toward World Class University - Dindin Jamaluddin; Tedi Priatna; Khaerul Umam; Epa Paujiah; D. Miharja; Asep Andi Rahman (Jurnal Manajemen Indonesia, 2021)
The rising global competition makes State Islamic University (UIN) Sunan Gunung Djati Bandung, to increase the quality of its institution toward World Class University. This study aims to describe the university policies and the recommended top priority programs for the next five years (2019-2023). This study was conducted in 2019 on the campus. The study used descriptive analysis and the result was analyzed based on Quacquarelly Symonds (QS) ranking. The data was gathered using a forum group discussion and field study. The field study was in the form of benchmarking on several universities in Indonesia. The result showed that the growth rate was constant, and it can be meassured that UIN Sunan Gunung Djati Bandung will become World Class University by 2029; It will have score 23 and will be in the 500 QS Asia World University ranking. Through annual programs and targets, UIN Sunan Gunung Djati Bandung can achieve its goals to be a world class university. Keywords—Higher Educational Institution; QS Ranking; UIN Sunan Gunung Djati; World Class University